Changes in Availability of Plant Nutrients during Composting of Cow Manure with Poplar Leaf Litter. Issue 4 (2nd October 2017) - Anwar, Zobia; Irshad, Muhammad; Bilal, Muhammad; Irshad, Usman; Hafeez, Farhan; Owens, Gary
ABSTRACT: Safe management of animal and plant waste is one of the world's most important environmental challenges. Composting has been proposed as a useful technique for beneficially recycling wastes. This study showed that significant temporal changes in the nutrient availability occurred during the composting of cow manure with poplar leaf litter within 120 days. In particular, total C in the final compost was directly related to the addition of tree litter and inversely related to the time of composting, whereas extractable P and NO3 increased with increasing amounts of tree litter and ammonium showed the opposite trend. During the later stages of the composting process higher concentrations of water soluble K, Ca, Mg, and Na were observed. The major benefit observed was that heavy metal concentrations initially present in the manure were significantly reduced during composting. Heavy metals in the final compost decreased in the order: Fe > Mn > Zn > Cu > Ni > Cd. The increased availability of plant nutrients following composting coupled with the lower extractability of heavy metals indicates that composting may be a sustainable option for agricultural waste recycling and increased productivity.